MANAJEMEN DATA POKOK PENDIDIKAN DALAM MENDUKUNG PROGRAM INDONESIA PINTAR DI SMA NEGERI 7 SINGKAWANG - Syahbani Syahbani; U. Husna Asmara; Sukmawati Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract Education basic data management is an activity carried out continuously in which planning, organizing, implementing, supervising, and evaluating in managing basic education data in support of smart Indonesia programs. This research aims to describe the planning, organizing, implementing, monitoring and evaluating dapodik in supporting PIP in Singkawang 7 Public High School. This research uses a qualitative approach to the type of case study. The research subjects were the head of Singkawang 7 Public High School, the deputy headmaster for student affairs, and the dapodik operator. Data collection methods by interview, documentation, and observation. Data analysis uses interactive data analysis namely data reduction, data display and verifications. Test the validity of the data with four criteria used, namely the test of credibility, transferability, dependability and confirmability. The results of the study, namely: 1) Planning is done through the establishment of school work programs and vice-principals in the field of student affairs, the determination of operator decree, utilization of dapodik guidelines, use of laptops with high specifications, adequate electricity, and fast internet, 2) Organizing is done by division of basic tasks and functions, 3) Implementation is carried out from data collection, inputting and data processing of students, students' proposals to receive PIP, checking and confirming data truths, dapodik delivery, and checking the number of students who get PIP, 4) Supervision is carried out by school principal, and 5) Evaluation is carried out to see which stage still needs improvement. Supervision activities should also be carried out by the Office of Education and Culture of West Kalimantan Province. The goal is that the activities carried out in accordance with the plan, also to minimize deviations and the results of supervision can be used as a basis for policy making. Keywords: Dapodik, Management, PIP